Dakwah Grup Musik Sholawat Metal di Pondok Pesantren Metal Tobat; Perspektif Psikologi - Beti Malia Rahma Hidayati (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2022)
Today's media in preaching is not only through lectures and recitations. Various ways are used by preachers to invite people to goodness, one of which is through music. Da'wah is still very minimally researched and the discussion is still warm. This study discusses the impact of the da'wah of the Sholmet music group from the perspective of music psychology. Data will be collected and processed according to qualitative research methods by extracting data through interviews, observations, and documentation. After the data is collected, the data is processed by data reduction analysis, data presentation, and verification. Then check the validity of the data by using the triangulation method. The results showed that the sholawat music he brought was a reminder to keep chanting sholawat at all times, as advice or a reminder of goodness, and develop oneself into a skill. Psychology describes the stimulus-response (SR) process as part of communication that can function as a way of modifying a person's behavior. Music is considered as an expression of emotion. By listening to certain music, a person can experience mood swings.